Voluntary detours : small-town and rural museums in Alberta - McTavish, Lianne, 1967- (McGill-Queen's/Beaverbrook Canadian Foundation studies in art history., 2021)
"After visiting hundreds of museums across Alberta, Lianne McTavish chronicles some of the most challenging and unexpected sites where the idea of the museum is being reshaped. The concept of the visit as a "voluntary detour" encapsulates the way visitors travel along backroads to find small town and rural museums, as well as the agreement to turn away from standard museum scripts when they arrive. Addressing themes of place, land, colonization, rurality, heritage, childhood, and play, McTavish reveals the museum visitor as multifaceted, with locals and tourists often interpreting museums very differently. Case studies include the World Famous Gopher Hole Museum, Fort Chipewyan Bicentennial Museum, Blackfoot Crossing Historical Park, and the Museum of Fear and Wonder. A key chapter analyzing sites devoted to resource extraction explores how these places promote settler colonial understandings of land use. By contrast, Indigenous museums and cultural centres defy colonial messages in displays that adapt and refuse conventional museum formats. Honouring local, rural, and Indigenous knowledge, Voluntary Detours enriches critical accounts of the past, present, and future of museums."--